PENGARUH KUALITAS SUMBER DAYA MANUSIA, KEPATUHAN SYARIAH, DAN INOVASI FINANCIAL TECHNOLOGY TERHADAP KINERJA KEUANGAN BANK PEMBIAYAAN RAKYAT SYARIAH (BPRS) DI INDONESIA - Muhammad Nabil Hisyam Ayyubi; Ahyakudin; Isti Nuzulul Atiah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the effect of human resource quality, sharia compliance, and financial technology (fintech) innovation on the financial performance of Islamic Rural Banks (BPRS) in Indonesia. The rapid development of the Islamic banking industry requires BPRS to continuously improve human resource quality, consistently implement Islamic principles, and optimize technological innovation in their operational activities. These factors are expected to enhance operational efficiency, service quality, and institutional competitiveness. This research employed a quantitative explanatory approach. The data were collected from the annual reports and financial statements of selected Islamic Rural Banks during the research period. Multiple linear regression analysis was used to examine the influence of the independent variables on financial performance. The findings indicate that human resource quality has a positive and significant effect on the financial performance of BPRS. Sharia compliance also positively affects financial performance by strengthening public trust, maintaining institutional credibility, and ensuring that all operational activities comply with Islamic principles. Furthermore, financial technology innovation significantly improves operational efficiency, expands financial service accessibility, and enhances customer service quality, thereby contributing positively to financial performance. Simultaneously, human resource quality, sharia compliance, and fintech innovation significantly influence the financial performance of Islamic Rural Banks. This study implies that improving human resource quality, strengthening sharia compliance, and maximizing digital technology utilization are essential strategies for enhancing the financial performance and competitiveness of Islamic Rural Banks in Indonesia.